A six-country comparison of the internet shopper profile - Brashear, Thomas G.; Kashyap, Vishal; Musante, Michael D.; Donthu, Naveen (Revista de Ciências da Administração, 2008)
As the Internet continues to evolve across the globe, the importance of understanding the similarities and dissimilarities among consumers in different regions is crucial for bothe marketing theory and practice. The authors report the characteristics of Internet shoppers in six countries (United States, England, New Zealand, China, Brazil, and Bulgaria). Internet shoppers and non-shoppers in these countries are profiled and compared on attitudes, motivations, and demographics. The work extends the research of Donthu and Garcia (1999) into an international realm and seeks to build on our current knowledge in this area. Findings show that online shoppers share many similar traits around the world. Internet shoppers in all the countries examined are similar with regard to their desire for convenience, are more impulsive, have more favorable attitudes towards direct marketing and advertising, are wealthier and are heavier users of both email and the Internet.